An Exploratory Content Analysis of Offender Concerns Before Incarceration. (September 2015) - Block, Steven; Ruffolo, Lyndsay
The time before entry into a correctional facility is stressful for most offenders. Yet, few studies have systematically considered the fears and concerns of persons entering jail or prison. This descriptive study uses an Internet message board forum to explore the central thoughts of individuals entering correctional institutions. A total of 344 posts are coded for key themes in written narratives. Ten categories are identified by researchers: relationships, possessions, violence and safety, medical concerns, self-improvement, privacy, responsibilities, prison conditions, boredom, and reputation. The potential impact of these pre-incarceration concerns on the actual prison experience is explored.